Compact tri‐notched wideband bandpass filter based on multiple resonances with wide upper stopband. Issue 12 (6th August 2020) - Wang, Chenhao; Xi, Xiaoli; Zhao, Yuchen; Shi, Xiaomin
Abstract: In this letter, a compact tri‐notched wideband bandpass filter based on stub‐loaded ring resonator (SLRR) and shorted stub‐loaded stepped impedance resonators (SSLSIR) with wide upper stopband is presented. The wideband characteristic is excited by coupling SLRR and SSLSIR with the arrangement of defected ground structures on the back of the substrate. By placing two sets of SSLSIRs inside and outside of the SLRR, three reflection poles can be formed in passband to introduce three notch bands with adjustable center frequencies. The quarter‐wavelength inter digital coupled lines are used to generate multiple transmission zeros to suppress high‐order harmonics to achieve a wide upper stopband characteristic. For validation, a wideband bandpass filter with a passband from 2.2 to 7.5 GHz and notch bands at 2.87, 5.69, and 6.5 GHz is fabricated. Measured results show that the 20 dB attenuation upper stopband can extend to 29 GHz.